2013
DOI: 10.3176/tr.2013.4.05
|View full text |Cite
|
Sign up to set email alerts
|

Learning for Entrepreneurship in Heterogeneous Groups: Experiences From an International, Interdisciplinary Higher Education Student Programme

Abstract: Although entrepreneurship education (EE) has gained popularity internationally, empirical work is scarce on the factors which influence the underlying learning process. This article presents the experiences of a European summer school where factors which contribute to entrepreneurial learning in interdisciplinary, intercultural student groups were elicited and analysed via student reflection. A total of 35 professional and scientific bachelor students from the Netherlands, Latvia and Estonia worked together in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 41 publications
0
22
0
4
Order By: Relevance
“…Moreover, non‐business university students have received limited attention in previous studies (Lans et al. ), despite the fact that this population represents the bulk of young adults pursuing an education program. Finally, there is no study regarding the impact of entrepreneurship education for Iranian universities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, non‐business university students have received limited attention in previous studies (Lans et al. ), despite the fact that this population represents the bulk of young adults pursuing an education program. Finally, there is no study regarding the impact of entrepreneurship education for Iranian universities.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is no agreement on what would constitute a welldefined method and a suitable conceptual model for assessing the effects of EEPs (Falkang and Alberti 2000;von Graevenitz, Harhoff, and Weber 2010). Moreover, nonbusiness university students have received limited attention in previous studies (Lans et al 2013), despite the fact that this population represents the bulk of young adults pursuing an education program. Finally, there is no study regarding the impact of entrepreneurship education for Iranian universities.…”
Section: Introductionmentioning
confidence: 99%
“…Different education levels, different demographic structures can be seen in classes. Lans et al (2013), found that heterogeneity including disciplinary and cultural differences -contributed to learning within the groups but also caused confusion and misunderstandings. Segmentation among audiences is meaningful because of having different learning needs and own characteristics (Ghosh and Bloch, 1994).…”
Section: E)mentioning
confidence: 99%
“…Collaborative problem-based learning encourages students to develop teamwork, collaboration, cooperation, critical thinking through analysis, synthesis, evaluation and reflection (Zhu et al, 2009). Cultural background may influence a student's understanding of the required collaborative processes and perceptions, and therefore, the required actions that are likely to be effective (Lans, Oganisjana, Taks & Popov, 2013). Postgraduate management students from different cultural backgrounds, ethnicities and nationalities may respond to educational styles differently (Selvarajah, 2006).…”
Section: What Do We Know About Cultural Perceptions About Online Educmentioning
confidence: 99%